Stroke treatment guided by transcranial Doppler monitoring in a patient unresponsive to standard regimens - Behrens, Stephan; Daffertshofer, Michael; Hennerici, Michael G. (Cerebrovascular diseases, 1999)
Today secondary prevention of stroke is based on large clinical trials with the disadvantage of a lack of individual pathophysiological aspects. This is mainly due to the difficulty in identifying the source of stroke reliably and rapidly in these patients. Recurrent microembolic events detected by transcranial Doppler monitoring (TCM) has been suggested to individualize treatment. We describe a patient with recurrent ischemic events in the posterior circulation. Repeated TCM of the PCA disclosed microembolic events in the course of an acute embolic lesion pattern demonstrated by MRI. Detection of high-intensity transient signals by TCM provided a useful guidance of pathophysiologically oriented treatment in this patient.
Gesehen am 21.07.2022